Origin Of Hypokinesia and General Impact on the Human Body (Eurasian Scientific Herald, 2022)
Hypokinesia can occur in the human body against the background of diseases of the nervous system (Parkinson's disease, Alzheimer's disease), as well as professional activities associated with a sedentary lifestyle (programmer, operator, accountant, etc.). On this basis, hypokinesia is classified into clinical, climatic-geographical and into types that develop in schoolchildren, depending on living conditions and professional activities. Especially in schoolchildren, it was noted that hypokinesia leads to a decrease in mental development.It is noted that hypokinesia (decrease in motor activity) leads to the induction of pathological morphofunctional changes in tissue cells of various organs in the body. In this case, hypokinetic syndrome develops under the influence of limited functional activity of skeletal muscles.